The Impact of A Lifestyle with Limited Physical Activity on Child Growth and Development in The Digital Era - Rizky Soemantri; Carsiwan; Sucipto (Universitas Negeri Semarang, 2026)
The rapid development of digital technology has significantly transformed children’s daily activities, with screen-based engagement increasingly replacing physical movement and direct social interaction. This shift has contributed to the early emergence of sedentary lifestyles, which may negatively affect children’s overall development. This study aims to examine the impact of low physical activity in the digital era on children’s physical, motor, psychological, and social development, as well as to identify strategies for balancing technology use with active behaviors. A Systematic Literature Review (SLR) was conducted using the Scopus database with the keywords physical inactivity, digital era lifestyle, sedentary behavior, and child development. Following PRISMA guidelines, the review process included identification, screening, eligibility, and inclusion stages. Of the 89 studies initially identified, 15 met the inclusion criteria and were analyzed. The findings indicate that increased exposure to digital media such as smartphones, online games, and social media is associated with reduced physical activity. This condition increases the risk of obesity, decreased motor competence, sleep disturbances, and psychological issues such as stress and loneliness. School-age children and adolescents are particularly vulnerable to these effects. Family supervision, digital parenting, and supportive environments play key roles in mitigating these risks. Overall, balanced technology use and active lifestyles are essential for children’s healthy development.